The Integral Assessment of the Financial Status and Creditworthiness of Communal Enterprises in Ukraine - Andrenko Olena A.; Mordovtsev Oleksandr S.; Mordovtsev Sergii M. (Bìznes Inform, 2020)
The article is aimed at developing a methodical approach to the integral assessment of the financial status of communal enterprises using the multidimensional statistical analysis method, since a comprehensive assessment of the activities of communal enterprises in the industry, which top the rating, will allow to use their achievements to solve the problems of enterprises-outsiders. It is concluded that the methods of calculating integral indicators presented in the Regulations developed by the NBU and the Ministry of Finance of Ukraine do not adequately reflect the true financial status and level of creditworthiness of enterprises. An approach to the integral assessment of the financial status is proposed, which involves building up a model of an integral index of the financial status of the enterprise; introduction and improvement of the information system for monitoring the financial-economic activities of enterprise; organization of a continuous comprehensive assessment and monitoring the main indicators that characterize the enterprise’s financial potential. The main stages of building up an integral index model using the main component method are described. An integral index, which characterizes the financial status of communal enterprises, is calculated and an industry rating of water supplying communal enterprises is compiled, allowing to respond in a timely manner to the deterioration of financial potential in the development of anti-crisis management solutions for enterprises-outsiders. Further research suggests improving the model through repeated testing for communal enterprises in various industries. This will allow to determine the final set of indicators to form the integral index.